THE USE OF GYMNASTICS EQUIPMENT IN INCLUSIVE PHYSICAL EDUCATION FOR STUDENTS WITH SPECIAL EDUCATIONAL NEEDS (Physical Culture and Sport: Scientific Perspective, 2025)
According to the concept of the New Ukrainian School, the process of implementing inclusion in secondary education institutions has now been intensified, inclusive classes are being created where students with special educational needs study together with ordinary children, attend physical education lessons together. In turn, an integral part of educational work in inclusive classes is physical education, and thanks to methodological features, one of the powerful means of inclusive physical education is gymnastics. Gymnastics and its means are widely represented in the curricula of the physical education branch, for schoolchildren of all age groups. Considering that in inclusive classes all schoolchildren, including those with special educational needs, study together, the aim of the article was a theoretical analysis of the use of gymnastics means in inclusive physical education of schoolchildren with special educational needs. The article highlights the means of gymnastics and gives examples of the use of gymnastics means in inclusive physical culture, namely - formation and general developing exercises, applied exercises and jumps, acrobatic exercises, free exercises and rhythmic gymnastics exercises, exercises on apparatus and gymnastic equipment, games and relays. The positive impact on the development of physical qualities, motor and coordination abilities, a positive impact on the formation of correct posture, as well as the development of moral and volitional qualities of "special" schoolchildren is noted. The scientific study notes that the use of gymnastics means should be carried out on the basis of general didactic and specific principles, in accordance with the age of schoolchildren, physical and mental capabilities, the development of physical and motor abilities, taking into account the concomitant diagnosis, and also have a corrective and developmental focus.
Keywords: gymnastics; gymnastics equipment; students with special educational needs; inclusive physical education